Comparison of 3d coral photogrammetry (cp) and coral video transect (cvt) for coral lifeform analysis using low cost underwater action camera - Ahmad, Zuhairi; Mohd Jinah, Muhammad Idzham Helmi; Saad, Shahbudin (2019)
This study evaluated the use of 3D Coral Photogrammetry (CP) and Coral Video Transect (CVT) images obtained from SCUBA divers for coral lifeform analysis using low- cost underwater action camera. Comparison were made between the datasets obtained from both methods on nine (9) transect within 4m x 7m area with different coral lifeform composition and percentage cover. Comparison of the CPCe statistical analysis shows that there are no significant differences (P < 0.05) between CP and CVT images where dead coral (P = 0.006), sand (P =0.011), and unknown (P = 0.002). However, the value for coral (P = 0.131) between CP and CVT are not significant. CP able to pro- duce prominent results for branching, massive and plate coral morphology. This implied that the 3D Coral Photogrammetry (CP) survey methods using low-cost action camera can produce acceptable results in terms of detecting coral lifeform. Improvement in camera quality hypothetically can produce higher precision of 3D coral images which suitable to be used for scientific research and management purposes. Other ad- vantages of using CP include the possibilities of 3D coral surveys using ROV, less field time and 3D coral seabed records for subsequent studies.